IInfluence of cropping systems on insect predators diversity and their trophic relationships - Maggio, Daniela Hipolito (2022)
Tropical agriculture areas are complex systems for management because they have a high diversity of species (mainly arthropods) interacting among them. The lack of knowledge about the species diversity and ecological interactions promotes the choice of simplistic agriculture practices and with negative impact in species community and environment (e.g. intense pesticide application). Ecological interactions between pests and their natural enemies (predators and parasitoids) are particularly interesting because may help adopting efficient and sustainable control strategies (e.g. conservative biological control). Using molecular markers and sequencing tools it is possible to analyze the predator gut content to identify with precision, which preys were ingested and find out if there are other ecological interactions such as intraguild predation. Thus, the aim of the present study was to evaluate the impact of different maize cropping systems on species richness and abundance, prey/predator interactions of important generalist maize predators. To achieve these objectives, five areas of organic and conventional corn were sampled in the state of São Paulo, with dry pitfall traps and active collection. Richness and abundance were analyzed using all samples. The main prey and predators had their DNA barcodes produced through the amplification of the COI gene. For the detection of predation, specific primers were designed for these most common pests in corn, and PCR reactions were performed with the intestinal contents of predators to detect the presence of pest DNA. Bioassays were done to identify the half-life of prey DNA in the gut of predators. To evaluate the impact of different farming systems on the food web, predators collected in dry pitfall traps and manual collection were used. DNA from the intestinal contents was extracted and then the Amplicon libraries were prepared for metabarcoding, and the sequences edited and compared with the sequences available at the NCBI by bioinformatics. The primers designed for Spodoptera frugiperda and Diabrotica speciose were efficient in prey amplification. It was possible to detect in the field the presence of predation by Coccinellidae and Doru luteipes on S. frugiperda. With metabarcoding it was possible to detect predation events in insects of no economic importance and only one species of agricultural pest. Intraguild predation events were detected mainly from Tachinidae in Harmonia axyridis and among coccinellids. Molecular tools are important to elucidate trophic interactions, allowing us to understand how species interact in the field. In addition, results such as those found here can help in future biological control work and also in integrated pest management.